A feasibility study af a blended learning dementia care: elective course for nursing students - Azam David Saifullah; Sri Mulyani; Eria Riski Artanti (UM Purwokerto Press, 2020)
As there is a limited long-term care options in Indonesia, people with dementia are cared for by their family. They often hospitalized as the condition progresses. Nurses are the profession with most contact. Therefore, preparing nursing students to care for people living with dementia is needed. Blended learning as e new learning strategy in dementia care for nursing student need to be evaluated to comprehend its feasibility in the future dementia care course. This study aimed to evaluate the feasibility of a blended learning course for nursing students about dementia. A blended learning course was developed as a three-credits elective course that voluntarily joined by 42 fourth year nursing students. This course integrates the schedule, modules, and assignments in a learning management system called eLOK (Moodle based). One group pre-post test was conducted to evaluate this course using DKAS (Dementia Knowledge Assessment Scale) and DAS (Dementia Attitude Scale) as instruments. Google form was integrated to evaluate the course and the use of eLOK. Data were analysed using a paired t-test. 37 students (88.1%) completed the questionnaires. There is a significant improvement in knowledge towards dementia (t = 5.96, p value < .00) but not the attitude (t = 2.50, p value = .17) right after completing the course. Students also well appreciated the quizzes and project as the evaluation of learning outcomes of the course. Moreover, the audio-visual material in eLOK made them feel helpful in learning new topics and made new constructive experience of learning. In conclusion, this blended learning is feasible to be used as a learning method for delivering dementia care course.